Water quality assessment of Sepang River based on physico-chemical analysis and phytoplankton community / Nur Farahin Mohd Ali - Nur Farahin , Mohd Ali (2017)
Water quality assessment of Sepang River based on physico-chemical analysis and phytoplankton community was carried out on monthly basis from May 2014 to February 2015 at 5 sampling stations. Water quality parameters that were analyzed were water temperature, pH, dissolved oxygen, turbidity, total dissolved solid, suspended solid, salinity, conductivity, biochemical oxygen demand, chemical oxygen demand, ammoniacal nitrogen, chlorophyll a, nitrate, nitrite, bromide, chloride, fluoride, sulphate and phosphate. Diversity of phytoplankton at the sampling stations was also examined. Based on the National Water Quality Standard of Malaysia (NWQS) and the results of this study, most of the water quality parameters of Sepang River are classified as moderate. Chloride, sulphate and nitrite present in the river are in high concentrations. A total of 59 species of phytoplankton with 6 main divisions were identified namely Bacillariophyta, Chlorophyta, Chrysophyta, Cyanobacteria, Pyrrophyta and Euglenophyta. The phytoplankton community was dominated by the division of Bacillariophyta and Chlorophyta. From the physical analysis using SPSS (Statistical Package for the Social Sciences) programme, phytoplankton has a negative response or correlation towards turbidity, suspended solid, COD, ammoniacal nitrogen, nitrate, phosphate and sulphate. In addition, from ANOVA analysis, only dissolved oxygen and salinity has shown a significant difference in between both stations and months. The values obtain from Shannon─Wiener formula indicated that high diversity of phytoplankton was found in the upstream of this river. Lastly, the overall water quality index for this river is 84.6 can be classified in class II which is considered as clean.